The Symptoms Of The Stagnation Of The Civil Case (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Symptoms of the progress of the civil case are events or facts that the lawsuit is exposed to in terms of form and before entering into the matter, and which lead to the suspension or temporary suspension of the proceeding in the case. There are certain symptoms that occur in the civil case, which make it in a state of temporary stagnation that prevents it from moving towards its desired goalAlso, some of these symptoms are due to involuntary causes that occur without the litigants having a hand in their occurrence, or the ability to push them. Such as death, loss of capacity, or loss of legal representative status